Implementasi Peraturan Walikota Nomor 16 Tahun 2021 Tentang Tarif Retribusi Parkir Di Tepi Jalan Umum - Anama, Rustam; Selanno, Hendry; J. Rolobessy, Mike (Jurnal Ilmiah Global Education, 2024)
Ambon City residents, who park their vehicles at Amplaz, are subject to parking fees in accordance with Ambon Mayor Regulation Number 16 of 2021 concerning Parking Retribution Tariffs on Public Roads. Amplaz is subject to progressive parking rates, as it is a zone. So that the tariff for four-wheeled vehicles is no longer RP3000, and two-wheeled vehicles are no longer Rp2000 as in the implementation of the previous Ambon Mayor Regulation. The party who manages parking at Amplaz always urges Ambon City residents to have awareness in paying parking rates according to Ambon Mayor Regulation Number 16 of 2021 concerning Parking Retribution Tariffs on Public Roads. There are many cases when Ambon City residents pay less retribution, arguing that there is no small money and only big money. Even reluctant to pay at all. However, it is advisable to have awareness in paying parking fees. The party who manages parking at Amplaz prioritizes parking service satisfaction. This is done by providing optimal services, namely; directing vehicles in an orderly manner into and out of the parking area, protecting the vehicle from loss of goods, damage due to bumps, and theft of spare parts. Likewise, the friendly behavior of the parking employees. As a result, Ambon City residents cooperatively pay parking fees, according to Ambon Mayor Regulation Number 16 of 2021 concerning Parking Retribution Tariffs on Public Roads.